2016
DOI: 10.1002/hipo.22670
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive stimulation results in long-term survival of newly generated hippocampal neurons in rats

Abstract: Electroconvulsive stimulation (ECS) is one of the strongest stimulators of hippocampal neurogenesis in rodents that represents a plausible mechanism for the efficacy of electroconvulsive therapy (ECT) in major depressive disorder. Using design-based stereological cell counting, we recently documented an initial 2.6-fold increase in neurogenesis following a clinical relevant schedule of ECS, a treatment also rescuing depression-like behavior in rats. However, these results gave no demonstration of the longevity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 51 publications
(80 reference statements)
5
32
1
1
Order By: Relevance
“…Finally, ECS and CRS + ECS have no effects on the total number of neurons and volume in the CA1, CA2/3 and hilus, or the volume of the entire hippocampus. In the context of our previous findings in the exact same animals (Olesen et al, , ), our compiled results show that CRS induces depression‐like behavior and hilar atrophy in rats, effects that are rescued following a clinical relevant schedule of ECS. Furthermore, CRS do not affect basal neurogenesis, the number of preexisting neurons in any hippocampal regions examined, or the volume of granule cell layer, CA1, CA2/3, or the entire hippocampus.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Finally, ECS and CRS + ECS have no effects on the total number of neurons and volume in the CA1, CA2/3 and hilus, or the volume of the entire hippocampus. In the context of our previous findings in the exact same animals (Olesen et al, , ), our compiled results show that CRS induces depression‐like behavior and hilar atrophy in rats, effects that are rescued following a clinical relevant schedule of ECS. Furthermore, CRS do not affect basal neurogenesis, the number of preexisting neurons in any hippocampal regions examined, or the volume of granule cell layer, CA1, CA2/3, or the entire hippocampus.…”
Section: Discussionsupporting
confidence: 80%
“…The present study is a direct continuation of two previous stereological studies from our laboratory subjecting rats to three weeks of chronic restraint stress (CRS) and/or a clinical relevant schedule of ECS (Olesen et al, ). Data from these studies showed that CRS induces a depressive‐like phenotype blocked by ECS (CRS + ECS).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…A recent study by Olesen and colleagues also suggested that ECS promotes long‐term survival of newly generated hippocampal neurons in rats (Olesen et al . ). However, in their study, BrdU was administered multiple times during ECS, so it could not be precisely distinguished whether the increase in BrdU(+) cells in the DG was because of the increase in proliferation or survival.…”
Section: Discussionmentioning
confidence: 97%
“…Preclinical studies involving rodents have sought to exploit the neuroplastic processes associated with ECS for antidepressant treatment. Such studies have demonstrated that ECS increases BDNF levels in the hippocampus and prefrontal cortex in rodents and induces hippocampal neurogenesis, enduring for up to 12 months . Treatment regimens that differ in frequency have been investigated to disentangle the impacts of these parameters on hippocampal neurogenesis.…”
Section: Discussionmentioning
confidence: 99%